Laporan Penelitian Kemasyarakatan Sebagai Bahan Pertimbangan Hakim Dalam Penjatuhan Pidana Terhadap Anak - Mataheru, Fioren; Lewerissa, Yanti Amelia; Tuhumury, Carolina (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Community research (LITMAS) is one of the main tasks of Correctional Centers (Bapas). This task is carried out by the Social Guidance Functional officer. This Litmas aims to provide recommendations in the process of resolving child cases.Purposes of the Research: Research Objectives: This study aims to find out whether social research reports have been used by judges as material for consideration in imposing crimes against children and what are the legal consequences of a judge's decision without considering social research reports.Methods of the Research: The research method used is normative juridical research where library materials are the basis for (knowledge) research which is classified as a secondary source material. The problem approach used is the statutory approach, the conceptual analysis approach and the case approach. The legal materials used are primary, secondary and tertiary legal materials. The collection technique used literature study as well as the processing and analysis techniques of legal materials by way of description using qualitative methods.Results of the Research: The research results show that social research reports have not been considered optimally because there are still judges' decisions that ignore social research results. This is not in accordance with the hope of realizing the best justice for the interests of children provided by the SPPA Law. Therefore, the Government as the legislator must explain in detail how social research reports must be considered, so that judges do not have different interpretations when deciding cases.